Ciprofloxacin-Loaded Polyvinylpyrrolidone Foils for the Topical Treatment of Wound Infections with Methicillin-Resistant Staphylococcus aureus (MRSA) - Fiorenza Rancan; Jana Jurisch; Sabrina Hadam; Annika Vogt; Ulrike Blume-Peytavi; Ilker S. Bayer; Marco Contardi; Christoph Schaudinn (MDPI AG, 2023)
Bacterial infections are a constant challenge in the management of acute and chronic wounds. Chronic wounds, such as diabetic foot ulcers, have increased significantly in the last few years due to the rise of an aging population. A better understanding of the infectious pathophysiological mechanisms is urgently needed along with new options for the treatment of wound infections and wound-healing disorders. New advances in the preparation of biocompatible dressing materials that can be loaded with antimicrobial drugs may improve the topical treatment of infected wounds. In this study, we investigated the antimicrobial activity of polyvinylpyrrolidone (PVP) foils loaded with ciprofloxacin (Cipro-foils) in the presence of acetic acid as a co-solvent. We used ex vivo human wounds that were infected with two bacterial strains: methicillin-resistant Staphylococcus aureus (MRSA) or Pseudomonas aeruginosa (PAO1). The effectiveness of the treatment was demonstrated by the quantification of the living bacteria extracted from the wound and the detection of released immunological mediators in skin extracts and in the skin culture media. We found that Cipro-foils effectively treated the infection with both PAO1 and MRSA. Other than PAO1, MRSA had no lytic activity toward skin proteins. MRSA infections increased cytokines' expression and release. Interestingly, treatment with Cipro-foils could partially counteract these effects.